Exploring the World of Social Policy : An International Approach - Hill, Michael J. (Michael James), 1937-; Irving, Zoë (Zoë M.) (Book collections on Project MUSE., 2020)
Authored by two highly respected and experienced academics, this book demonstrates the rewards of studying social policy from an international perspective by avoiding the constraints of a single-nation focus.